Międzynarodowe aspekty controllingu w spółkach zależnych - Czyczerski, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents various forms of an international business engagement. It describes opportunities and threats resulting from the acquisition or foundation of a foreign subsidiary. It points at controlling as an excellent tool which can support leading the subsidiary. The fact, that controlling focuses its attention on the future and co-ordination aspects, makes it possible to respect expectations of the group as well as the goals of the foreign subsidiary. The complexity of the process of internalization sets special requirements to the controlling. It has to manage the challenges resulting from an international business environment such as various reporting systems, various currencies, country risk, cultural differences. None of the above mentioned remains without impact - sometimes not easy to discern - on the controlling. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 72-79